Wonderboompoort, South Africa: A natural game funnel for meat harvesting during the later Acheulean. (October 2021) - Lombard, Marlize; Lotter, Matt G.; Caruana, Matthew V.
Highlights: We demonstrate that the Magaliesberg range forms a topographic barrier with Wonderboompoort being a narrow gap. Through this gap herds were naturally funnelled while migrating between optimal grazing zones. This landscape context indicates the site's potential as meat-harvesting site during the Pleistocene later Acheulean in South Africa. Abstract: We revisit Wonderboompoort, South Africa, in terms of its potential to have served as a natural game funnel during the Pleistocene later Acheulean. The geological and ecological time depth of the Magaliesberg landscape, allows us to use the current setting as suitable proxy for understanding past animal and early human land use. We formulate a set of four criteria for natural game-funnelling landscapes. Testing Wonderboompoort against these criteria, we demonstrate that the Magaliesberg range forms a topographic barrier with the pass or 'poort' as a narrow gap with adjacent lookout points across grazing plains and into the valley. Our hydro-analyses demonstrate how the locality provided a permanent, predictable water source and access to wetland zones north and south of the mountain. Quartzite outcrops in a sheltered valley with direct evidence of flake quarrying for later Acheulean tool knapping contributes to the strategic attraction of the Wonderboom landscape for early humans within a diverse and rugged biotope. Our parsimonious interpretation is that the Wonderboom landscape may serve as model example of a natural game-funnel, and that meat harvesting – instead of weapon-assisted hunting – remains plausible until evidence to the contrary is found.